2022
DOI: 10.1101/2022.10.04.510646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

α-synuclein fibril and synaptic vesicle interactions lead to vesicle destruction and increased uptake into neurons

Abstract: Monomeric alpha-synuclein (aSyn) is a well characterised as a lipid binding protein. aSyn is known to form amyloid fibrils which are also localised with lipids and organelles in so called Lewy bodies, insoluble structures found in Parkinson s disease patient s brains. It is still unclear under which conditions the aSyn-lipid interaction can start to become pathological. Previous work to address pathological interactions has focused on using synthetic lipid membranes, which lack the complexity of physiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 89 publications
(121 reference statements)
0
2
0
Order By: Relevance
“…We have shown that amyloid formation of αSynΔN7 is not stimulated by liposome binding (Fig. 4), in marked contrast to αSynWT, wherein lipid acts as a substrate for its assembly into amyloid, with the fibril yield and rate of assembly depending on the LPR (3335). Lipids can become integrated into the core of the cross-β amyloid fold (33), being clearly observed in the cryo-EM structures of the resulting fibrils (36).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…We have shown that amyloid formation of αSynΔN7 is not stimulated by liposome binding (Fig. 4), in marked contrast to αSynWT, wherein lipid acts as a substrate for its assembly into amyloid, with the fibril yield and rate of assembly depending on the LPR (3335). Lipids can become integrated into the core of the cross-β amyloid fold (33), being clearly observed in the cryo-EM structures of the resulting fibrils (36).…”
Section: Discussionmentioning
confidence: 93%
“…Binding of αSyn to membranes is not only important for its physiological function, but may also be critical in terms of the pathological mechanism of aggregation and Lewy body formation. Lipid membranes can trigger αSyn amyloid fibril formation (3235), and lipids are incorporated into the fibril structures (35, 36). Together with evidence that lipids are a major component of Lewy bodies (37), this suggests that lipid-catalysed amyloid fibril formation may be involved in the aetiology of synucleinopathies.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have revealed that exogenous α-synuclein induces Lewy body pathology and lead to a decrease in synaptic protein, reduced synaptic activity, and altered spine dynamics prior to neuron loss [11,12,24]. Some studies have shown that α-synuclein PFFs and oligomers directly interact with membranes and synaptic vesicles, modulating calcium transients and vesicle homeostasis [25][26][27]. Here, we assessed the synaptic changes that occur during the propagation of α-synuclein in a neural network by measuring sEPSCs in the somatosensory cortex after PFF injection into the striatum, finding a decrease in the frequency of spontaneous events and a concomitant decrease in synapse density.…”
Section: Discussionmentioning
confidence: 99%